Peningkatan Kreativitas, Efektivitas, dan Minat Siswa dalam Pembelajaran Menulis Naskah Drama dengan Model Pembelajaran Berbasis Masalah - Nina Fatmawati (Universitas Suryakanca, 2017)
This article describes the improvement of students' creativity in learning to write drama script with Problem-Based Learning model (PBM). The research method used is Classroom Action Research. The results showed that students 'creativity, learning effectiveness, and students' interest experienced improvement in each cycle. The average value of student creativity cycle I 75,95, cycle II 86,59, and at cycle III 95,45. Based on the KKM determined that 75, cycles I, 19 students (43.18%) is not complete and 25 students (56.82%) thorough, cycle II, 36 students (81.82%) complete and 8 students (18.18%) is incomplete, and cycle III of all students is complete. Then, the effectiveness of learning also increases. The average value of teacher activity cycle I 2.05 (enough), cycle II 3.27 (good), and in cycle III 3.82 (very good). The average value of student activity in cycle I 2.05 (enough), on cycle II 3 (good), and on cycle III 3.68 (very good). In addition, student interest in learning also increased. The average score of student interest in cycle I 78.92 began to grow (MB), the average value of student interest questionnaire in cycle II 85.91 MB, and the average value of student interest questionnaire in cycle III 92.39 with the information already entrust (SM). Keywords: Writing drama script, creativity, effectiveness, interest.